Effects of crown-root angle on stress distribution in the maxillary central incisors’ PDL during application of intrusive and retraction forces: a three-dimensional finite element analysis - Heravi, Farzin (Prog Orthod, 2013)
BACKGROUND: Different crown-root angulations of maxillary central incisors can be assumed as a potential reason for many underscored outcomes of orthodontic treatments. The aim of this study was to determine the effects of the different crown-root angles on stress distributions in the maxillary central incisor’s periodontal ligament (PDL) during application of intrusive and retraction forces using a 3D finite element method. METHODS: Two models of a maxillary central incisor were constructed using ANSYS software: the first one with an angle of 166.7° (as a sample of the maxillary central incisor in a class II, division 2 patient) and the other one with an angle of 173.4° (normal angulation). Each of the samples was loaded twice by an intrusive force (0.25 N) and a retraction force (0.5 N) through the ideal position of brackets. RESULTS: FEM results showed little difference between stress distributions in the two models during intrusion (ten thousandth) compared to retraction (thousandth). In the application of retraction force, the stress concentration on the curved tooth was less than the other. CONCLUSION: To produce similar patterns of stress in the PDL, orthodontists can apply 1.18 times heavier retraction forces on the maxillary central incisors in class II, division 2 patients compared to class I patients.